2007
DOI: 10.1038/nature05895
|View full text |Cite
|
Sign up to set email alerts
|

Low Atlantic hurricane activity in the 1970s and 1980s compared to the past 270 years

Abstract: Hurricane activity in the North Atlantic Ocean has increased significantly since 1995 (refs 1, 2). This trend has been attributed to both anthropogenically induced climate change and natural variability, but the primary cause remains uncertain. Changes in the frequency and intensity of hurricanes in the past can provide insights into the factors that influence hurricane activity, but reliable observations of hurricane activity in the North Atlantic only cover the past few decades. Here we construct a record of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 30 publications
10
103
0
1
Order By: Relevance
“…The spatial pattern of Mg/Ca SST correlation decreases toward the eastern and southern tropical Atlantic, and hence the correlation divergence at this time. Additionally, the number of major hurricanes was reduced during the 1970s and 1980s relative to earlier parts of the record [Nyberg et al, 2007]. If the post-1970 data are removed, the Mg/Ca SST record is strongly correlated to the number of hurricanes and tropical storms (r = 0.83, p < 0.082 after accounting for the reduced degrees of freedom resulting from smoothing the data sets).…”
Section: Tropical Atlantic Ssts and Hurricanesmentioning
confidence: 88%
“…The spatial pattern of Mg/Ca SST correlation decreases toward the eastern and southern tropical Atlantic, and hence the correlation divergence at this time. Additionally, the number of major hurricanes was reduced during the 1970s and 1980s relative to earlier parts of the record [Nyberg et al, 2007]. If the post-1970 data are removed, the Mg/Ca SST record is strongly correlated to the number of hurricanes and tropical storms (r = 0.83, p < 0.082 after accounting for the reduced degrees of freedom resulting from smoothing the data sets).…”
Section: Tropical Atlantic Ssts and Hurricanesmentioning
confidence: 88%
“…Declining luminescence trends has likely affected the interpretation of past erosion records. Nyberg et al (2007) show multiple cores with declining luminescence intensity trends, which they relate to a decreasing trend in hurricane activity. The findings presented here suggest that such declining trends may alternatively reflect declining coral densities, perhaps in response to the same cause.…”
Section: Discussionmentioning
confidence: 99%
“…A previous work also suggested that peaks and trends of major north Atlantic hurricane activity concur with lower total solar irradiance, i.e. lower solar activity, and vice versa, in several period between 1730 and 2005 (Nyberg et al, 2007). Some papers include besides the SN other solar activity-associated phenomena.…”
Section: Examples Of Current Work Relating Space Weather and Hurricanesmentioning
confidence: 99%
“…A warming response in the upper troposphere to increased solar UV forcing decreases the atmosphere convective available potential energy leading to a weaker cyclone (Elsner and Jagger, 2008). General circulation models suggest a mechanism that impacts the baric atmospheric properties; the models show that changes in the stratosphere, induced by interactions between UV and ozone may penetrate down to the troposphere affecting winds and sea level pressure (Shindell et al, 2001); during solar maximum the increased solar radiation increases sea level pressure, which would result in weaker easterly winds and therefore weaker vertical wind shear promoting more hurricanes (Nyberg et al, 2007). In this context, the good relations found between hurricanes and SN would be due to the close relation between SN and solar radiation.…”
Section: The Total and Uv Solar Radiationmentioning
confidence: 99%